ARCHIGESH-21. The place where the Earth rounds up - Grigoryeva, Elena (project baikal, 2021)
The article tells us about the events of the 16th Forum of architects-mountain skiers, which was held in Sheregesh in March 2021. The participants of the working meetings exchanged information and discussed topical issues of regional organizations of the Union of Architects of Russia. The article presents the list of the winners of the ski, table tennis and billiard competitions.
Keywords: ARCHIGESH; Sheregesh; architecture; sport; conference of planners and architects